Ownership and strategic choice of HR methods by Chinese SMEs - Zheng, C.; O'Neill, Grant; Morrison, M. (Curtin University of Technology. School of Economics and Finance, 2007)
Using a sample of seventy-four Chinese small and medium-size enterprises (SMEs), this paper explores the influence of ownership on human resource management (HRM) practices by SMEs. It concludes that enterprise ownership determines both strategic choice and the level of complexity in the application of HRM practices, which are more likely to be adopted by foreign-related and domestic, private-owned companies than by collective and state-owned enterprises.